Highly Efficient Organic Solar Cells with Improved Vertical Donor–Acceptor Compositional Gradient Via an Inverted Off‐Center Spinning Method. Issue 5 (2nd December 2015) - Huang, Jiang; Carpenter, Joshua H.; Li, Chang‐Zhi; Yu, Jun‐Sheng; Ade, Harald; Jen, Alex K.‐Y.
Abstract : A novel, yet simple solution fabrication technique to address the trade‐off between photocurrent and fill factor in thick bulk heterojunction organic solar cells is described. The inverted off‐center spinning technique promotes a vertical gradient of the donor–acceptor phase‐separated morphology, enabling devices with near 100% internal quantum efficiency and a high power conversion efficiency of 10.95%.